Intergenic interactions and genetic polymorphism in increasing the probability of alcoholic dependence - Snytkov, Evgenii V.; Kipen, Vyacheslav N.; Kazachok, Aleksandr V.; Melnov, Sergei B. (Experimental Biology and Biotechnology, 2021)
The results of molecular genetic analysis of 13 polymorphic variants of genes, according to the data of genome-wide association studies (GWAS) associated with the development of addictive states, in the group of persons with alcohol dependence (n = 142) and in the comparison group (n = 211) are presented. The main genotyping method is polymerase chain reaction (PCR) followed by high resolution melting (HRM) and clustering of melting profiles; the melting results are validated using the restriction fragment length polymorphism (PCR-RFLP) method. As a result, single nucleotide polymorphisms associated with an increased likelihood of alcohol dependence are genotype GG (rs7085104, AS3MT); genotype GG (rs7590720, PECR); allele C (rs11191580, NT5C2); allele T (rs17504622); allele A (rs73229090, EPHX2); allele A (rs1109501, MUC7 ).